ANALYSIS OF CONTROLLING FACTORS IN THE FORMATION OF RESERVOIR PROPERTIES OF THE TOMORI FORMATION AND ITS IMPLICATIONS FOR THE QUALITY OF RESERVOIR ROCK, TIAKA FIELD CENTRAL SULAWESI - Fakhrul Dzakirin, Darojatun
The Tiaka Field is a clastic limestone reservoir, operated by JOB Pertamina-Medco Tomori Sulawesi, has a recovery factor of less than 10% which indicates low oil production compared to the Initial Hydrocarbon In-Place. This is suspected to be due to poor reservoir properties and high heterogeneity in the limestone reservoir. The average porosity per well is 9.5%, while permeability ranges from 0.001 – 300 mD. The wide range of permeability values suggests diverse factors influencing the reservoir properties in the Tiaka Field. The field is located in the collision zone between Australia and Sulawesi, resulting in a foreland basin and a series of thrusting structures. The aim of this study is to identify the geological factors influencing reservoir properties, analyze their effects, and examine the relationships between the controlling factors. The methods used in this study are geological structure analysis, core analysis, and well data analysis. Geological structure analysis is conducted using palinspastic reconstruction to determine the geometry of the Tiaka Field structure, followed by fracture modeling to determine the fracture population in the Tiaka Field area. The next method is core analysis. This involves megascopic analysis of the core to identify sedimentation features and lithofacies, followed by microscopic description to identify microfacies and diagenesis analysis of petrographic samples. The final method is well data analysis. This is conducted to correlate the results of core analysis to wells without core sample data, which can then be used to create a depositional environment model across the entire Tiaka Field. The results of this study are, based on palinspastic reconstruction, the Tiaka Field has a fault propagation-fold structure geometry with a total shortening of 26% from normal conditions, and based on balancing section reconstruction, a balanced section is obtained with a depth to detachment correlation value of 0.9847. Core analysis also produces 12 lithofacies, which are then grouped into three facies associations or depositional environments: interior platform, estuarine deposits, and platform margin. Diagenesis processes play a role in increasing or decreasing porosity. The diagenesis processes that can be identified through thin section analysis are micritization, dissolution, recrystallization, cementation, compaction, and dolomitization. These diagenesis processes occur in marine, meteoric, and burial diagenesis environments. The factors controlling the properties of the Tiaka Field are proven to be interconnected, from deposition to tectonics. The deposition of Tomori Formation carbonate rocks in certain depositional environments produces lithofacies that function as storage in the reservoir. Diagenesis processes influence reservoir quality, either by increasing porosity through dissolution and dolomitization, or by decreasing porosity through loading and fracture filling. Tectonic processes play a role in the formation of fault-propagation fold structures that trap hydrocarbons and cause the development of open fractures.